DIMENSI EKONOMI DALAM PEMBANGUNAN NEGARA BANGSA - ghazali, Ahmad (Islamic Economics and Business Faculty of UIN Antasari, 2012)
This article examines the economic dimension in the development of a nation, espe-cially Indonesia. In developing a nation, the common goal of having a nation-state will become aguide to unify the people. For Indonesia, the issue of development has been central, althoughother aspects of nation life are by no means less important. It is development that drives thedynamics of governance. Very often, there is a strong emphasis on economic development only.Although theoretically the economy does influence positively the development of a nation-state,the legal certainty cannot be ignored. Both are two sides of the same coin that need to be presentfor the citizens of a country to prosper.